Introduction to 2020-3 - Buch, Anders (Nordic Journal of Working Life Studies, 2020)
This issue of Nordic Journal of Working Life Studies brings together four articles. The first article of this issue, Cherry Picking Disablility Rights? Swedish Disability Policy on Employment, Health and Participation, authored by Faten Nouf-Latif and colleagues, examines how Swedish disability policies are developed to meet UN Conventions on the Right of Persons with Disabilities. Focusing on a recent Swedish governmental disability policy document and legal documents, the authors ask how they describe individuals with disabilities in terms of citizens in the policy areas of health and employment?; how governmental responsibilities are formulated?; and how the policy management affects individuals’ opportunities to enjoy citizenry and participation? Using directed content analysis and theories of social risk and governance, the authors observe that the employment domain is given much more attention and focus at the cost of the policy area of health. Hard governance is predominant in relation to the employment domain, whereas governance in relation to the health domain is softer – employing abstract directives to stakeholder organizations and authorities (...)